The Effects of Domain Experience and Task Presentation Format on Accountants' Information Relevance Assurance - Vera-Mun˜oz, Sandra C.; Kinney, William R.; Bonner, Sarah E. (The Accounting Review, 2001)
Information relevance advisory services offer growth opportunities for accountants in CPA firms, but we know little about the types of knowledge needed to provide high-quality advice. In a two-stage experiment, accountants with different management and public accounting experiences (that we suggest lead to different types of knowledge) receive task information in alternative formats, and develop relevant information for a client's decision. We find that participants are more likely to choose an appropriate problem representation when they receive an appropriate task format or when they have more management or public accounting experience (stage one). Also, when participants choose an appropriate problem representation, more management accounting experience improves their development of relevant information, but more public accounting experience does not (stage two). Our results suggest that tailored task presentation and domain experience that facilitates acquisition of multiple knowledge types improve accountants' information relevance advice.